Effect of weight percentage on physical and mechanical properties of coconut shell reinforced polymer composite - Zakaria, Kamarul Ariffin; Tar, Vishaldeep; Yusuff, Mohd Asri; Roseli, Adnan; Ali, Mohd Basri; Tajul Arifin, Ahmad Mubarak (Asian Research Publishing Network, 2023)
The utilization of natural fibers in composites has been increasing and developed to save the environment by using biodegradable materials. Synthetic fiber has many disadvantages than natural fiber such as lower mechanical properties, high cost, and higher environmental risk. Therefore, this study aims to develop natural fiber composites that are reinforced with coconut shell waste and study the effect of weight percentage (wt%) on their physical and mechanical properties. Testing samples were produced from coconut shell reinforced and polyester resin matrix. Coconut shell powder with a particle size of 500 μm and below is randomly distributed into polyster resin matrix. The coconut shell wt% varies from 10% to 30%. The physical and mechanical properties of the composite are determined by collecting data from the density test, hardness test, and tensile test performed based on ASTM standards. The finding results showed that the physical and mechanical properties of coconut shell reinforced polymer composite are influenced significantly by the wt% of coconut shell. The maximum tensile strength was achieved at 15% wt% of the coconut shell.